Low plasma 25(OH) vitamin D level is associated with increased risk of COVID‐19 infection: an Israeli population‐based study - Merzon, Eugene; Tworowski, Dmitry; Gorohovski, Alessandro; Vinker, Shlomo; Golan Cohen, Avivit; Green, Ilan; Frenkel‐Morgenstern, Milana (The FEBS journal, 2020)
Vitamin D deficiency is a worldwide pandemic. The aim of this study was to evaluate associations of plasma 25(OH)D levels with the likelihood of coronavirus disease 2019 (COVID‐19) infection and hospitalization. The study population included the 14 000 members of Leumit Health Services, who were tested for COVID‐19 infection from February 1st to April 30th, 2020, and who had at least one previous blood test for the plasma 25(OH)D level. ‘Suboptimal’ or ‘low’ plasma 25(OH)D level was defined as plasma 25‐hydroxyvitamin D, or 25(OH)D, concentration below the level of 30 ng/mL. Of 7807 individuals, 782 (10.02%) were COVID‐19‐positive, and 7025 (89.98%) COVID‐19‐negative. The mean plasma vitamin D level was significantly lower among those who tested positive than negative for COVID‐19 [19.00 ng/mL (95% confidence interval (CI) 18.41–19.59) vs. 20.55 (95% CI: 20.32–20.78)]. Univariate analysis demonstrated an association between the low plasma 25(OH)D level and increased likelihood of COVID‐19 infection [crude odds ratio (OR) of 1.58 (95% CI: 1.24–2.01, P < 0.001)], and of hospitalization due to the SARS‐CoV‐2 virus [crude OR of 2.09 (95% CI: 1.01–4.30, P < 0.05)]. In multivariate analyses that controlled for demographic variables, and psychiatric and somatic disorders, the adjusted OR of COVID‐19 infection [1.45 (95% CI: 1.08–1.95, P < 0.001)] and of hospitalization due to the SARS‐CoV‐2 virus [1.95 (95% CI: 0.98–4.845, P = 0.061)] were preserved. In the multivariate analyses, age over 50 years, male gender and low–medium socioeconomic status were also positively associated with the risk of COVID‐19 infection; age over 50 years was positively associated with the likelihood of hospitalization due to COVID‐19. We concluded that low plasma 25(OH)D levels appear to be an independent risk factor for COVID‐19 infection and hospitalization. Vitamin D deficiency is recognized as a significant health concern in which there is heightened interest because of the potential impact on COVID‐19 risk. In a landmark study involving a large Israeli population, Milana Morgenstern and colleagues found that the plasma level of vitamin D is lower among individuals who have tested positive for COVID‐19 and have been hospitalized. This indicates that low vitamin D status is an independent risk factor for severe COVID‐19; male gender and low‐medium socioeconomic status were also shown to be positively associated with the risk of infection. Moreover, age (being > 50 years old) was associated with COVID‐19 hospitalization.